Organic lead toxicology - Patocka, Jirí (Acta medica (Hradec Kralove), 2008)
Lead is one of the oldest known and most widely studied occupational and environmental poison. Despite intensive study, there is still debate about the toxic effects of lead, both from low-level exposure in the general population owing to environmental pollution and historic use of lead in paint and plumbing and from exposure in the occupational setting. Significant position have organic lead compounds used more than 60 years as antiknock additives in gasoline. Chemical and toxicological characteristics of main tetraalkyl leads used as gasoline additives are discussed in this article. The majority of industries historically associated with high lead exposure have made dramatic advances in their control of occupational exposure. However, cases of unacceptably high exposure and even of frank lead poisoning are still seen, predominantly in the demolition and tank cleaning industries. Nevertheless, in most industries blood lead levels have declined below levels at which signs or symptoms are seen and the current focus of attention is on the subclinical effects of exposure. The significance of some of these effects for the overt health of the workers is often the subject of debate. Inevitably there is pressure to reduce lead exposure in the general population and in working environments, because current studies show that no level of lead exposure appears to be a 'safe' and even the current 'low' levels of exposure, especially in children, are associated with neurodevelopmental deficits.
Keywords: Environmental Exposure; vystavení vlivu životního prostředí; Humans; nemoci z povolání; Lead; lidé; olovo; Lead Poisoning; otrava olovem; Occupational Diseases